Comparison of the antioxidant activity of Malaysian ginger (Zingiber officinale Roscoe) extracts with that of selected natural products and its effect on the viability of myoblast cells in culture - Nur Fatin Nabilah Mohd Sahardi,; Faizul Jaafar,; Siti Nor Asyikin Zakaria,; Tan, Jen Kit; Mariam Firdhaus Mad Nordin,; Suzana Makpol, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Ginger has been proven to possess various therapeutic effects, including antibacterial, anticancer, anti-inflammatory, and antioxidant effects. However, data on the comparison of ginger antioxidant activity with that of other natural products are still lacking. This study aimed to analyse and compare the antioxidant properties of two types of Malaysian ginger extracts (GE1 and GE2) with that of selected natural products. The antioxidant activities were measured by 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) and ferric reducing antioxidant power (FRAP) assays, while cell viability was determined by 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfonyl)-2H-tetrazolium (MTS) assay. The order of the DPPH scavenging activities was as follows: vitamin C > palm tocotrienol-rich fraction (TRF) > α-tocopherol > N-acetylcysteine (NAC) > Ficus deltoidea > butylated hydroxytoluene (BHT) > Centella asiatica > GE2 > GE1 > Moringa oleifera > Kelulut honey; the order of the mean FRAP value was as follows: NAC > α-tocopherol > BHT > TRF > Ficus deltoidea > Moringa oleifera > GE2 = GE1 > Centella asiatica > Kelulut honey. The viability assays showed that both ginger extracts significantly increased the percentage of viable cells (p < 0.05). In conclusion, neither of the ginger extracts was cytotoxic toward cells and both possessed comparable antioxidant properties, indicating their potential for ameliorating oxidative stress.